Perspektif Hukum Ekonomi Islam Tentang Jual Beli Flash Sale Di Shopee - Wati, Ai; Putri, Meily Indriani (Jurnal Hukum Ekonomi Syariah, 2023)
Shopee Flash Sales is a promotion from Shopee that offers exclusive offers for a limited time and limited number of products. The price set in the Flash Sale promo can be said to be a very affordable price because price set is not the normal price but tends to be cheap. In the Flassh Sale promo, Shopee tries to implement a fair sale and purchase that not detrimental to both the seller and the buyer. However, the Flash Sale strategy should be questioned when the product offered has a very limited supply but consumers or interested parties flock from all over Indonesia, resulting in a gap in product supply with a large number of consumers. The formulation of the problem in this research is what is the meaning of Flash Sale? What is the mechanism for buying and selling Flash Sale on the Shopee application? and What is the perspective of Islamic economic law regarding buying and selling Flash Sale on the Shopee application? So this study aims to determine the meaning of Flash Sale and the mechanism of buying and selling Flash Sale in the Shopee application and to find out the perspective of Islamic economic law regarding the sale and purchase of Flash Sale in the Shopee application. This research is included in the type of qualitative research with data collection techniques used, namely interviews, observation, and documentation. The data were analyzed through the stages of data reduction, data presentation, then drawing conclusions. Based on the results of this study it was found that the mechanism for buying and selling Flash Sale in the Shopee application is basically the same as buying and selling online as usual. In the perspective of Islamic economic law, buying and selling Flash Sale in the Shopee application is included in the Ba’i As-Salam contract. In addition, the sale and purchase has fulfilled the pillars and conditions of sale and purchase and is in accordance with the principles of buying and selling, so buying and selling Flash Sale in the Shopee application is permissible and halal.